Pengaruh Privasi, Keamanan, Kepercayaan dan Pengalaman Terhadap Niat Untuk Bertransaksi Secara Online - Palungan, Pither (Ekonomika, 2010)
The purpose of the study are: (1) examine the influence of confiedence in the attitude of consumers to transact on line. Test the influence of risk perseption on consumer attitudes to online transaction; (2) examine the influence of consumer attitudes on intentions to transact on line; (3) examine the influence of trust in risk perseption, (4) examine the influence of perseptions of privacy risks; (5) test influence of risk perseption on intention to transact online; (6) test the effects of behavioral control on intention to transact online; (7) test the influence of subjective norm on intention to transact on line; (8) examine the influence of perseptions of security risks; (9) To test the influence of experience using the intenet for online purchase intentions. Analysis tools using Partial Least Square (PLS). The research found that the trust provides a positive influence on attitudes are not significant, security providing a positive influence and significance of risk perseption; belief that positive impact is not significant to the perception of risk to transact online; privacy positive impact and significant risk perception; perceptions of risk provides a positive impact and significant manner, attitude a positive impact and significant to intention to transact online; perseptions of risk provides a positive impact and significant intentions, experience using the Internet to effect positive and significant impact on the intention; norm subjective negative impact is not significant; control behavior gives a significant positive affect on intentions. Â Key Words: Risk Perception, Online Transactions, Privacy, Security trust